2018
DOI: 10.3389/fimmu.2018.00517
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Epithelial–Mesenchymal Transition Regulator Hepatocyte Growth Factor Receptor/Met on Skin Immunity by Modulating Langerhans Cell Migration

Abstract: Langerhans cells (LCs), the epidermal dendritic cell (DC) subset, express the transmembrane tyrosine kinase receptor Met also known as hepatocyte growth factor (HGF) receptor. HGF is the exclusive ligand of Met and upon binding executes mitogenic, morphogenic, and motogenic activities to various cells. HGF exerts anti-inflammatory activities via Met signaling and was found to regulate various functions of immune cells, including differentiation and maturation, cytokine production, cellular migration and adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 104 publications
(135 reference statements)
1
29
0
1
Order By: Relevance
“…Moreover, LC migration from the skin to sdLN in both the steady-state and during inflammation is not altered in the absence of E-cadherin. The downregulation of E-cadherin is a molecular hallmark of a genetic program called EMT, which plays important roles in embryonic development, wound healing, and tumor invasion (Sagi and Hieronymus, 2018). Indeed, it has been suggested that EMT also controls LC development, adhesion, and/or migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, LC migration from the skin to sdLN in both the steady-state and during inflammation is not altered in the absence of E-cadherin. The downregulation of E-cadherin is a molecular hallmark of a genetic program called EMT, which plays important roles in embryonic development, wound healing, and tumor invasion (Sagi and Hieronymus, 2018). Indeed, it has been suggested that EMT also controls LC development, adhesion, and/or migration.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin deficiency does not enhance LC emigration from the skin LC attach themselves via homophilic E-cadherin binding to the surrounding keratinocytes (Tang et al, 1993) and downregulate E-cadherin during their migration, but whether this is cause or consequence of LC mobilization and maturation remains unknown. Moreover, E-cadherin downregulation on LC is associated with a broader genetic program known as epithelial-to-mesenchymal transition (EMT) (Hieronymus et al, 2015;Konradi et al, 2014;Sagi and Hieronymus, 2018). Thus, we determined whether the loss of E-cadherin influences EMT marker expression and LC migration.…”
Section: Lack Of E-cadherin Leads To a More Rounded Lc Cell Body And mentioning
confidence: 99%
“…More recently a subpopulation of CD8 positive cytotoxic T-cell has been found to express MET, further linking its pathway to a role in tumor immunity [20]. Moreover, HGF has been linked to increased expression of PD-L1 in dendritic cells and CTLA-4 in T-cells, with a role in the induction of immune tolerance [6,21].…”
Section: Discussionmentioning
confidence: 99%
“…Langerhans cells in skin express a broad range of epithelial-like adhesive molecules that permit the functional integration into the keratinocyte layer. This includes tight junction proteins, such as claudin-1 and ZO-1/Met signaling in skin resident DCs including LCs appears to be a critical determinant for maintaining normal immune function and as an important constituent that interlaces tissue regenerative functions with the appropriate immune responses that must be accomplished [47] .…”
Section: Emt and Wound Healingmentioning
confidence: 99%